2015
DOI: 10.1007/s00125-015-3664-y
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of thyroid peroxidase autoantibody levels in type 1 diabetes: evidence from discordant twin pairs

Abstract: Aims/hypothesis The discordance status of (autoimmune) type 1 diabetes within monozygotic twin pairs points to the importance of environmental factors. The aim of this study was to investigate whether the environmental events causing type 1 diabetes influence thyroid autoimmunity. Methods Monozygotic and dizygotic twins discordant for type 1 diabetes from the UK and USA were tested for thyroid peroxidase autoantibodies (TPOA) by radioimmunoassay. Using quantitative genetic model fitting of a liability-thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
1
3
1
Order By: Relevance
“…Nevertheless, the environmental overlap was large, with 10–18% of the variance attributable to factors shared across the disorders but unique to individuals. Our findings contrast with results from a co-twin control analysis by Wang et al ( 33 ) that did not find evidence of association between type 1 diabetes and thyroid peroxidase autoantibodies (TPOab) over and above shared factors in twin pairs (i.e. shared genetic and environmental influences).…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, the environmental overlap was large, with 10–18% of the variance attributable to factors shared across the disorders but unique to individuals. Our findings contrast with results from a co-twin control analysis by Wang et al ( 33 ) that did not find evidence of association between type 1 diabetes and thyroid peroxidase autoantibodies (TPOab) over and above shared factors in twin pairs (i.e. shared genetic and environmental influences).…”
Section: Discussioncontrasting
confidence: 99%
“…Of interest, the risk for TPOA in adolescence was increased if children had developed IA or TGA and remained increased in children with the high-risk HLA genotypes, suggesting some, but incomplete, overlap in genetic and environmental determinants of the autoantibodies. This is consistent with previous twin studies that showed that heritability of thyroid autoimmunity is .50% (31,32) and that heritability includes additive genetic factors and environmental factors that are different for TPOA compared with IA (31).…”
Section: Discussionsupporting
confidence: 92%
“…While ADM is a major component of the organ‐specific autoimmune disease group, we know little of the risk of autoimmunity in Chinese patients and how it predisposes to other autoimmune diseases. As with studies in white populations, TPO autoantibody positivity was higher both in people with ADM (17.7%) and, in particular, in women, whether they had ADM or not (22.1%) . To date, data on 21‐OH and tTG autoantibodies in ADM are scarce, both in China and elsewhere.…”
Section: Discussionmentioning
confidence: 82%
“…As with studies in white populations, 12,14 TPO autoantibody positivity was higher both in people with ADM (17.7%) and, in particular, in women, whether they had ADM or not (22.1%). 27 To date, data on 21-OH and tTG autoantibodies in ADM are scarce, both in China and elsewhere. The biopsy-positive and serum-positive prevalence of coeliac disease tend to be low among Asians in general (0.5% and 1.6%, respectively) 28 , while autoimmunity (positive results in assays for anti-tTG IgA and anti-DGP-IgG) was only 0.06%.…”
Section: The Prevalence Of T1d In China Differs From Western Countries;mentioning
confidence: 99%